The Role of Catholic Religious Education Teachers in Developing Students’ Spirit of Diakonia - Ery Yurenti; Paulina Maria Ekasari Wahyuningrum; Edy Jumrio (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to describe the role of Catholic Religious Education (CRE) teachers in developing students spirit of diakonia, the implementation of diakonia values in learning, and its supporting and inhibiting factors at the elementary and junior high school levels of the Siswarta Foundation, Palangka Raya Representative. The study employed a qualitative descriptive-interpretive approach. Data were collected through non-participatory observation, semi-structured interviews, and documentation involving seven informants consisting of the principal, CRE teachers, and students selected purposively. Data were analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing, along with triangulation. The results show that the role of CRE teachers is carried out through three channels, namely the integration of learning materials, everyday exemplary conduct, and persuasive guidance. Diakonia values are implemented explicitly in lesson plans and teaching modules using contextual methods, Problem-Based Learning, and experiential learning adjusted to each level, reinforced by routine service activities and post-activity reflection. Supporting factors include school policies, collaboration among teachers, and the personal vocation of educators, whereas the inhibiting factors are limited time, families academic orientation, and gadget dependence. The study concludes that diakonia has become a distinctive feature of Catholic schools, yet the consistency of teacher exemplarity and the equal distribution of reflection still need to be strengthened